(untitled) (Journal of Energy and Safety Technology (JEST), 2022)
Prolonged or intense exposure to heat can lead to a range of health effects. This study evaluated environmental heat exposure, heat-related symptoms, and acute physiological changes among 39 farmers in Kelantan, Malaysia. During the end of the monsoon season in February to Mac 2019, wet bulb globe temperature (WBGT) was collected in the farm environment to assess heat exposure. Blood pressure, heart rate, and body core temperature were measured pre-, mid and post-shift to measure the physiological response of farmers towards environmental heat. Sociodemographic, occupational information and heat-related symptoms that subjects had experienced were gathered using a questionnaire. The WBGT outdoor showed a high risk for heat stress and strain (> 28.0 oC) based on the American Conference of Governmental Industrial Hygiene (ACGIH) threshold limit values (TLVs). More than half (50%) of farmers reported heat-related symptoms including fatigue, lethargy, dizziness, rashes, and cramps. Significant physiological changes including heart rate, body temperature, and systolic blood pressure occurred across the work shift (p <0.05). However, no significant association (p>0.05) was found between the Acute Health Symptoms score (AHSS) with associated factors, thus no statistical model was further developed. In conclusion, farmers experienced significant psychological changes across the work shift. Preventive and control measures for heat stress are needed to reduce the risk of heat strain.